Tackling Whiteness in organizations and management. Issue 4 (6th May 2014) - Al Ariss, Akram; Özbilgin, Mustafa; Tatli, Ahu; April, Kurt
Abstract : Purpose: – The purpose of this paper is to offer a theoretical and methodological framework to overcome knowledge gaps on Whiteness in organizational and management studies. Design/methodology/approach: – The paper draws on a brief review of literature on ethnic privileges. Findings: – The authors propose a relational approach to tackling ethnic privileges in organizations and management research. Research limitations/implications: – The framework contributes to a better understanding and deconstruction of ethnic privileges at work. Originality/value: – The paper proposes a theoretical and a methodological framework for tackling Whiteness in organizational and management studies. By doing so, it elucidates the topic of Whiteness, bringing new insights from an interdisciplinary perspective.